Chinese drama in Singapore : yesterday, today and tomorrow. - Tan, Edgar Ti Seng. (2008)
This project is a practical planning and implementation paper, which looks to better position MediaCorp Chinese language dramas in the overseas television market. MediaCorp's efforts to export its Chinese language drama serials overseas have largely been unsuccessful despite a burgeoning marketplace and network's initiatives into international co-productions. To date, MediaCorp has failed to find the right formula for global success. The paper will outline an action plan or strategy for Chinese language drama production in MediaCorp.